Effect of MoSi2 addition on ablation behavior of ZrC coating fabricated by vacuum plasma spray. Issue 8 (1st June 2018) - Liu, Tao; Niu, Yaran; Li, Chong; Zhao, Jun; Zhang, Jimei; Zeng, Yi; Zheng, Xuebin; Ding, Chuanxian
Abstract: To improve the ablation resistance of ZrC coating, MoSi2 incorporated ZrC composite coatings were fabricated by vacuum plasma spray. The ablation resistance of the composite coatings was evaluated using a plasma jet with a heat flux of 1.94 MW/m 2 . The phase compositions and microstructures of the coatings before and after ablation were investigated, and the ablation mechanisms and effect of MoSi2 were analyzed based on thermal dynamics and microstructure changes. Results showed that MoSi2 addition could improve the ablation resistance of ZrC coating by means of decreasing the surface temperature and changing the microstructure of the oxidation layer. Si derived from the decomposition of MoSi2, which occurred within coating, was beneficial to maintain the thickness and integrity of the SiO2 layer and reduce the oxygen pressure beneath. The thickness of the SiO2 layer was related to the formation rate (Vf ) and the consumption rate (Vc ) of SiO2 . The diffusion of Si was in favor of increasing the value of Vf . MoSi2 could be one choice to improve the ablation resistance of the ZrC coating.